AN EXPERIMENTAL STUDY ON THE EFFECTIVENESS OF PEER FEEDBACK COMPARED TO TEACHER-WRITTEN CORRECTIVE FEEDBACK IN TEACHING WRITING - Diemas Aditya Briansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study focuses on examining the effectiveness of peer feedback (PF) and teacher-written corrective feedback (TWCF) in improving the writing accuracy of eighth grade students at MTs Negeri 1 Jembrana, Bali. The main objective of this study was to determine which feedback method has a greater impact on students' ability to write accurately. A total of 40 students were divided into two groups: an experimental group that used peer feedback and a control group that received written feedback from the teacher. A quasi-experimental approach was used to measure students' writing ability before and after the intervention through a pre-test and post-test. The test was designed to assess vocabulary and grammar accuracy. The results obtained were analyzed using statistical methods, including independent sample t-test and paired test. The results showed a significant improvement in the experimental group, with the average score increasing from 66.25 in the pre-test to 82.75 in the post-test. In contrast, the control group showed a smaller increase, from a mean score of 67.25 in the pre-test to 74.50 in the post-test. Statistical analysis showed a p-value of 0.003, indicating a statistically significant difference between the two groups at the 5% level of significance. Based on these results, the study concluded that peer feedback was more effective than written corrective feedback from teachers in helping to improve students' writing accuracy.